Kontroversi bunga bank dan riba: implikasi terhadap keadilan ekonomi syariah di era modern - Wifaqi, Hikmah (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the controversy of interest and usury along with its implications and solutions for Islamic economic justice in the modern era. This research method uses a qualitative method with a literature study approach. The result of this research is that there are differences in scholarly opinion regarding the law of bank interest and usury. Most of the scholars forbid it but some others allow it with some criteria. The implication of interest and usury is that it can cause economic injustice and increase the burden of debt in society. The solution to the problem is to offer a sharia economic system such as mudharabah and musyarakah and free from economic injustice and adhere to Islamic teachings.